2020
DOI: 10.1111/josh.12902
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization and e‐Cigarette Use among Middle and High School Students

Abstract: BACKGROUND Bullying has been associated with several adverse health outcomes, including substance use. However, little is known about the association between bullying and e‐cigarette use. This study examined the association between bully victimization and the frequency of e‐cigarette use. METHODS Data from the 2016‐2017 Canadian Student Tobacco, Alcohol and Drugs Survey were used (N = 49,543). The target population consists of Canadian students enrolled in grades 7‐12. Multivariable logistic regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
6
11
0
Order By: Relevance
“…In general, the findings from this German sample are in line with the data reported from a large representative Canadian sample of students of grades 7–10 (Azagba et al, 2020) and also with the results of a US student survey conducted among sexual minority youth (Doxbeck, 2020), which indicated that bullying victimization is associated with higher odds of e‐cigarette smoking.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, the findings from this German sample are in line with the data reported from a large representative Canadian sample of students of grades 7–10 (Azagba et al, 2020) and also with the results of a US student survey conducted among sexual minority youth (Doxbeck, 2020), which indicated that bullying victimization is associated with higher odds of e‐cigarette smoking.…”
Section: Discussionsupporting
confidence: 90%
“…In another study bullying victimization among Canadian students was associated with higher odds of past 30‐day e‐cigarette use. Additionally, authors reported that those students that were bullied daily or almost daily were more likely to use e‐cigarettes more frequently compared to nonbullied students (Azagba et al, 2020). Data from the 2017 National Youth Risk Behavioral Survey indicate an association between vaping and increased violence victimization.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, research investigating factors such as loneliness and bullying in terms of using ATPs is sparse; thus, our findings contribute to the existing knowledge regarding what characterises young adolescents with diverse tobacco use patterns. Our findings concerning the relationships between well-being characteristics and diverse tobacco use patterns are, like those of most existing studies, not unidimensional (Azagba et al, 2020;Dyal & Valente, 2015;Lindström & Rosvall, 2018;Niño et al, 2016;Varga & Piko, 2015;Vieno et al, 2011), which may underpin the complex associations between well-being and tobacco use -especially considering the social implications of tobacco use behaviours (e.g., Engels & ter Bogt, 2001). Tobacco use may be used as a means to feel included in a group, e.g., because they are exposed to other peers' smoking.…”
Section: Discussionsupporting
confidence: 73%
“…The literature is somewhat inconsistent in regard to how adolescents’ well-being is associated with ATP use. One study found that loneliness was not related to using e-cigarettes ( Lindström & Rosvall, 2018 ), while another study found experience with being bullied was associated with higher odds for using e-cigarettes ( Azagba et al, 2020 ). These well-being measures are associated with engagement in other risk behaviours, i.e., binge drinking and smoking conventional cigarettes, although the directions of the associations are not unidimensional ( Dyal & Valente, 2015 ; Niño et al, 2016 ; Varga & Piko, 2015 ; Vieno et al, 2011 ).…”
mentioning
confidence: 99%
“…Ragavan et al (2020) found positive associations between the two when examining lifetime use, however, the relationship did not remain statistically significant when other substances—alcohol, tobacco, and marijuana—were introduced. Similarly, Azagba et al (2020) found that bullying victimization was associated with e-vape use, and when stratified by sex, found that, though statistically significant among both sexes, girls who were victimized were at higher odds of e-vape use. Doxbeck (2020) found that school bullying victimization was not associated with e-vape use, whereas electronic bullying victimization was linked to increased e-vape use.…”
Section: Illicit Substance Use Among Adolescents In the Usmentioning
confidence: 92%